Strategi Peningkatan Daya Saing Potensi Lokal melalui Pelatihan Pemasaran Digital di Desa Padarincang Provinsi Banten - Zuhdi, Rasyid; Karenina, Aziza; Putri, Winda Rachman; Usnia, Andyta Ma’rifatul; Febrian, Andika; Fattahillah, Nuris (Abdibaraya, 2025)
The development of information technology has significantly transformed the ways in which individuals interact, conduct transactions, and consume products across much of Indonesian society. With Indonesia’s population reaching approximately 224.3 million people and internet usage encompassing around 97% of the population, there has been a notable shift from conventional marketing towards digital marketing across various sectors, including micro, small, and medium enterprises (MSMEs). Competence in information technology has now become a determining factor in all aspects of life, particularly within the industrial sector. Padarincang Village, located in Banten Province, is recognised as a region with considerable potential in MSME-based production of emping melinjo, which remains relatively productive, though its current target market is limited to the local community and still relies on conventional methods. The digital literacy gap represents a tangible challenge faced by villagers, while simultaneously, the shift in consumer behaviour towards digital platforms presents opportunities for both local and global markets. The primary aim of this community engagement initiative is to enhance the competitiveness of MSME-based emping melinjo products in Padarincang Village, Banten Province. The training programme is designed to provide practical knowledge of digital marketing strategies, encompassing the introduction of social media, creative content creation, utilisation of e-commerce platforms, and brand management for increased product appeal. The implementation methods include identifying participants’ needs through preliminary surveys, preparing training materials tailored to the context of emping melinjo products, delivering instructional sessions, and facilitating hands-on practice in producing digital promotional media. This activity has proven to enhance the community’s digital literacy, increasing from 30% to 85%. It is expected to serve as a step towards building a sustainable digital marketing ecosystem, enabling UMKM products such as emping melinjo from Padarincang Village, Banten Province, to be marketed more widely on a national as well as global scale, and ultimately contribute to improving the local community’s economy.